2019
DOI: 10.1039/c9dt00079h
|View full text |Cite
|
Sign up to set email alerts
|

Telluraporphyrinoids: an interesting class of core-modified porphyrinoids

Abstract: This perspective presents a concise overview of the developments in telluraporphyrinoid chemistry since its inception.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 49 publications
1
28
0
Order By: Relevance
“…Treatment of 4 with hydrochloric acid afforded vacataporphyrin 7 , and ditelluraporphyrins were used to prepare dideazaaporphyrins (divacataporphyrins). , Ditelluraporphyrins have also been used to generate metallaporphyrins such as 8a , b . Recently, investigations into telluraporphyrin-type structures have attracted renewed interest and new examples have been reported, including tellurabenziporphyrins and ditelluradiazuliporphyrins …”
Section: Introductionmentioning
confidence: 99%
“…Treatment of 4 with hydrochloric acid afforded vacataporphyrin 7 , and ditelluraporphyrins were used to prepare dideazaaporphyrins (divacataporphyrins). , Ditelluraporphyrins have also been used to generate metallaporphyrins such as 8a , b . Recently, investigations into telluraporphyrin-type structures have attracted renewed interest and new examples have been reported, including tellurabenziporphyrins and ditelluradiazuliporphyrins …”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the tellurophene-containing dithiasapphyrin was not reported. Our group has recently focused interest in the synthesis and studies of tellurophene-containing porphyrinoids because of their unusual and unique properties . Herein, we report the synthesis of tellurophene-containing dithiasapphyrins, and our studies indicated that the tellurophene ring in telluro dithiasapphyrin is in the normal orientation facing toward the inner core unlike the other hetero dithiasapphyins, in which the corresponding heterocycle was inverted and facing outward from the macrocycle core.…”
Section: Introductionmentioning
confidence: 99%
“…Heteroporphyrins resulted from replacing one or two pyrrole Ns with other heteroatoms such as O, S, Se, Te, C, Si, and P, which exhibit interesting physicochemical properties that are different from tetrapyrrolic porphyrins. Thus, substituting pyrrole ring(s) of porphyrins with other heterocycles such as furan, thiophene, selenophene, tellurophene carbacycle, etc.…”
Section: Introductionmentioning
confidence: 99%